2011
DOI: 10.18061/1811/52950
|View full text |Cite
|
Sign up to set email alerts
|

Negative Emotion in Music: What is the Attraction? A Qualitative Study

Abstract: Why do people listen to music that evokes negative emotions? This paper presents five comparative interviews conducted to examine this question. Individual differences psychology and mood management theory provided a theoretical framework for the investigation which was conducted under a realist paradigm. Data sources were face-to-face interviews of about one hour involving a live music listening experience. Thematic analysis of the data was conducted and both within-case and cross-case analyses were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 60 publications
6
60
1
1
Order By: Relevance
“…Consequently, some people may be more aware than others of the negative impact listening to sad music can have on their moods. Whatever the reason, the evidence suggests that some people do like to immerse themselves in negative emotions despite its negative consequences, even seeming to be "addicted" to such experiences (Garrido & Schubert, 2011). The fact that some ruminators claim that immersion in negative emotions is enjoyable, is a fascinating finding.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, some people may be more aware than others of the negative impact listening to sad music can have on their moods. Whatever the reason, the evidence suggests that some people do like to immerse themselves in negative emotions despite its negative consequences, even seeming to be "addicted" to such experiences (Garrido & Schubert, 2011). The fact that some ruminators claim that immersion in negative emotions is enjoyable, is a fascinating finding.…”
Section: Discussionmentioning
confidence: 99%
“…The high degree of integration of personal experiences of ambivalence with the emotions perceived in the object follows the notion of simultaneous absorption and dissociation (Garrido & Schubert, 2011), and the positive experiences of negatively valenced artifacts can be seen as a safe way of experiencing negative emotions, distinctive to personal experiences. This study showed that similar to music, visual art objects function as mirrors to reflect one's current state.…”
Section: Examples Of Such Contradictions Includedmentioning
confidence: 92%
“…This question becomes more interesting still when considered in relation to depression. Australian scholar, Sandra Garrido, has focussed on the ways that depressed people ruminate with sad music (Garrido & Schubert, 2012). She describes the involuntary bias that people with clinical depression have towards negative stimulation, and theorises that this may lead to a diminished ability to dissociate from the feelings of sadness that are evoked from the music, where nonruminators may be able to appreciate the sadness without experiencing it.…”
Section: Katrina Saysmentioning
confidence: 99%